Effect Of ZnO Seed Layer On The Growth Of ZnO Nanorods Via Solution Precipitation Method - Nik Jusoh, Nik Anis Hafiza (Universiti Sains Malaysia, 2018)
There are various types of substrates that have been used to grow ZnO nanorods on the surface. However, it is difficult to obtain highly aligned ZnO nanorods on Si substrate because of the large mismatches between ZnO and Si. This problem could be addressed by depositing a highly (002) oriented ZnO seed layer on the surface of Si substrate. The seed layer of ZnO improved the coverage and aligned growth of ZnO nanorods. In this project, ZnO seed layers were deposited on the Si substrate using spin coating followed by post annealing in air. The precursors were zinc acetate dihydrate dissolved in ethanol. The deposition of the seed layer was done at different cycles of coating and different rotational speed (rpm) to improve the coverage of ZnO nanorods.The SEM images shows that the highest number of coating cycles (11 cycles) and lowest rpm (1000 rpm) has the best ZnO nanorods surface coverage on the substrate. For 1000 rpm, the percentage of ZnO nanorods surface coverage is 82.2%, while for 1000rpm at 11 coating cycles was 84.42%. The result showed that the lowest speed and highest number of coating cycles provided the best coverage of ZnO seed layer. Next, ZnO nanorods were synthesized from the pre-deposited ZnO seed layer via solution precipitation method. Different annealing temperatures on the ZnO seed layer were conducted to observe the differences of the alignment. The ZnO nanorods grown at 350oC showed the best vertical alignment as the nanorods grew at c-axis.